Serendipitous actinomycosis infection mimicking malignant lesion in carcinoma of unknown primary - Sayak Choudhury; Archi Agrawal; Swapnil Rane; V Rangarajan (World Journal of Nuclear Medicine)
Actinomycosis is a bacterial infection caused by Actinomyces species that are commensal in the human oral cavity, digestive tract, and genital tract. The present case highlights actinomycosis of the hypopharynx, mimicking malignancy in 18F-fluorodeoxyglucose positron emission tomography-computed tomography.